Antigua and Barbuda. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Antigua and Barbuda during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as apiculture, veterinary, public-private sector cooperation, sheep farming, greenhouses, seedling use, pest control, technology, food security and safety, resilience against climate change, climate-smart agriculture, using solar energy. Likewise, work was done to improve the coconut and citrus value chains, as well as bread production, by using sweet potatoes and cassava to replace starch in bread preparation. Finally, women were integrated into the agricultural sector, through the Network of Women Producers and supported in the revitalization of the sector, after the damage caused by hurricanes Irma and María.